Pemberdayaan Lansia dalam Melakukan Pijat Kaki untuk Mengurangi Nyeri Rheumathoid Arthritis di UPTD Pelayanan Sosial Lanjut Usia Binjai Tahun 2024 - Petra Diansari Zega; Adelina Sembiring; Ali Imran Sirait; Yurnita Batee; Abdul Hafizh Alrasyid Siregar (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Rheumatoid arthritis (RA), a chronic inflammatory autoimmune disorder, is characterized by persistent synovial inflammation, erosion of bone and cartilage, leading to joint destruction. It can attack the joints and other parts of the body such as tendons, ligaments, and bones. In serious cases, it can affect other organs such as the lungs, heart, nervous system, and eyes. Foot massage is effective to reduce pain. Before implementation of foot massage, the average pain scale was 6 (moderate pain). After implementation of foot massage the pain scale decreased to 2 (mild pain). Through empowering the elderly, the elderly are taught and assisted in performing safe and effective foot massage techniques to reduce pain, improve blood circulation, and reduce joint stiffness due to rheumatoid arthritis. The conclusion of this community service activity shows that the use of foot massage is effective for patients with rheumatoid arthritis who experience pain.